Tourism mobilities and urban change: geographies of transnational gentrification - Buhr, Franz (2024)
This chapter explores recent scholarly contributions in the field of urban change and tourism mobilities in order to contextualise the emergence of transnational gentrification. The chapter argues that although there are contexts where tourism alone takes a dominant role in urban transformation, the impact of tourists upon urban space cannot be fully divorced from other coexisting transnational mobile populations who also gravitate towards gentrifying neighbourhoods. What we usually call gentrification in touristic cities seems rather to be produced by a global compact of young local middle classes and privileged mobile dwellers, including tourists and higher-income residents, transnational and national gentrifiers, and various profiles of short-term city users. The chapter brings forth research findings examining the relationship between short-term rentals and gentrifying urban contexts, as well as the consumption patterns of an increasingly mobile transnational middle class.